Pandemi COVID-19 dan Gebu CSR pada Perusahaan Adaro Energy - Arizah, Ainun; Darwin, Khadijah; Ramly, Ramly; Abbas, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research aims at disclosing the decision made by PT. Adaro Energy in conducting the donation during the pandemic of COVID-19 and understand the donation in boosting the business image. The type of this research is qualitative employing the semiotics approach. The object of this research is the narrative text in terms of CSR obtained from website and social media of Adaro Energy. The result of this research discloses that Adaro Energy is active to synergy with the various stakeholders along the pandemic of COVID-19 through the distribution of the number of donations. It is successful to boost good image of firm so that Adaro Energy can obtain the legitimacy in the form of certificate appreciated by the National Agency for Disaster Management.